Achieving Compliance when Legal Sanctions are Non-Deterrent - Jean-Robert Tyran; Lars P. Feld (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Law backed by non-deterrent sanctions (mild law) has been hypothesized to achieve compliance because of norm activation. We experimentally investigate the effects of mild law in the provision of public goods by comparing it to severe law (deterrent sanctions) and no law. The results show that exogenously imposing mild law does not achieve compliance, but compliance is much improved if mild law is endogenously chosen, i.e. self-imposed. We show that voting for mild law induces expectations of cooperation, and that people tend to comply with the law if they expect many others to do so.
Keywords: C92; D72; K42; 330; Deterrent effect of legal sanctions; Expressive law; Social norms; Public goods; Voting